Molecular hydrogen in sports medicine: New therapeutic perspectives - Ostojic, S. M. (International Journal of Sports Medicine, 2015)
In the past 2 decades, molecular hydrogen emerged as a novel therapeutic agent, with antioxidant, anti-inflammatory and anti-apoptotic effects demonstrated in plethora of animal disease models and human studies. Beneficial effects of molecular hydrogen in clinical environment are observed especially in oxidative stress-mediated diseases, such as diabetes mellitus, brain stem infarction, rheumatoid arthritis, or neurodegenerative diseases. A number of more recent studies have reported that molecular hydrogen affects cell signal transduction and acts as an alkalizing agent, with these newly identified mechanisms of action having the potential to widen its application in clinical medicine even further. In particular, hydrogen therapy may be an effective and specific innovative treatment for exercise-induced oxidative stress and sports injury, with potential for the improvement of exercise performance. This review will summarize recent research findings regarding the clinical aspects of molecular hydrogen use, emphasizing its application in the field of sports medicine.